2013
DOI: 10.1248/cpb.c13-00400
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of the Cytotoxic Activities of Some Isatin Derivatives

Abstract: A series of isatin derivatives, 1-butyl-5/7-chloro/fluoro-3-((4-methoxybenzyl)imino)indolin-2-ones (3a-d), 6-butyl-chloro/fluoro-6H-indolo[2,3-b]quinoxalines (4a-h), and 5/7-chloro/fluoro-3-((4-methoxybenzyl)imino)-indolin-2-ones (5a-h) were synthesized and characterized by using Fourier transform (FT)-IR, 1 H-and 13 C-NMR spectroscopy, mass spectrometric and elemental analysis. The substances were further subjected to in vitro cytotoxicity evaluation against HeLa, SK-BR-3, and MCF-7 cells. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recently, Reddy et al reported the synthesis of chloro/fluoro‐substituted 6‐ N ‐butyl‐6 H ‐indolo[2,3‐ b ]quinoxalines, which exhibited significant in vitro cytotoxic activity against HeLa cells . To the best of our knowledge, the synthesis of bromo‐ and tert ‐butyl‐functionalized indolo[2,3‐ b ]quinoxaline derivatives is still unprecedented.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Reddy et al reported the synthesis of chloro/fluoro‐substituted 6‐ N ‐butyl‐6 H ‐indolo[2,3‐ b ]quinoxalines, which exhibited significant in vitro cytotoxic activity against HeLa cells . To the best of our knowledge, the synthesis of bromo‐ and tert ‐butyl‐functionalized indolo[2,3‐ b ]quinoxaline derivatives is still unprecedented.…”
Section: Resultsmentioning
confidence: 99%
“…Isatins have been reported in the literature to possess cytotoxic effects across a range of microorganisms and various cancer cell lines. The mechanism of cytotoxic action of isatins is unknown, and it is tempting to speculate that one mechanism of cytotoxicity is due to the depletion of AIR resulting in the inhibition of purine biosynthesis. While plausible, the reactivity of isatins with biological sulfhydryl groups complicates the determination of the effect of isatin on purine biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The biological data used in this study was the anti-cancer activity against MCF7, (in terms of -log IC 50 ), of a set of 109 isatin derivatives [43][44][45][46][47][48][49][50][51]. The data set was classified into calibration and prediction set by kenardston algorithm of the 20 prediction molecules from the spaces of the calculated descriptors.…”
Section: Data Setmentioning
confidence: 99%